Final answer:
Given that ∠A and ∠B are a linear pair and their measures are x° and (2x - 3)° respectively, the sum of these angles will equal 180°. Solving for x gives x = 61. Substituting x back into the expression for ∠B gives ∠B = 119°.
Step-by-step explanation:
Given that ∠A and ∠B form a linear pair and the values of ∠A and ∠B are x° and (2x - 3)° respectively, we know that the sum of angles of a linear pair is always 180°. Thus, we set up the equation: x + 2x - 3 = 180 which simplifies to 3x - 3 = 180. Adding 3 to both sides gives 3x = 183 and then dividing both sides by 3 gives x = 61. Substituting x back into the expression for ∠B gives ∠B = 2*61 - 3 = 119°
Learn more about Linear Pair of Angles